East and West Entangled (17th-21st Centuries) (Firenze University Press, 2024)
«History has to reorient», as the historian and sociologist Andre Gunder Frank observed. In the global or globalised age, a culture is no longer regarded as a discrete entity, but rather as a hybrid formation that interacts with other cultures in an incessant process of multidirectional exchange. Bringing together «Eastern» and «Western» case studies ranging from the seventeenth to the twenty-first centuries, this volume reminds historians that to conduct transcultural analyses they need to be alert to the multiple ways, comic intents included, in which difference is negotiated within contacts and encounters – from selective appropriation to rejection or resistance.